Association of gastrointestinal parasitism with physiological parameters in improved sheep of Junín Region, Peru - Arauco Villar, Fernando (2021)
The association of gastrointestinal parasitism with body weight, haematocrit and the FAMACHA method was determined in Junín sheep (lambs and rams) from the Stud group of SAIS Túpac Amaru Ltda. No. 1, Junín Region, Peru. The study was carried out in two seasons: May (dry) and October (rainy). In total, 109 rams and 98 lambs were sampled in May and 89 rams and 85 lambs in October 2018. There was a negative correlation between the haematocrit and the transformed value of parasite load. All the animals were positive to gastrointestinal parasites, finding a higher parasite load in males in October and in May in females. In May there were more cases of animals resistant to parasitism than in October. The highest frequency of gastrointestinal parasites was Nematodirus (50%), followed by Trichostrongylus (25%) and Ostertagia (15%).